2003
DOI: 10.7326/0003-4819-139-1-200307010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Extended Oral Anticoagulant Therapy after a First Episode of Pulmonary Embolism

Abstract: Patients with pulmonary embolism have a substantial risk for recurrence after discontinuation of oral anticoagulation, regardless of treatment duration. Physicians should try to identify patients who are at high risk for recurrent venous thromboembolism and are therefore potential candidates for indefinite oral anticoagulant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
197
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 354 publications
(216 citation statements)
references
References 16 publications
9
197
1
9
Order By: Relevance
“…One study on PE27 and a second study on DVT28 have reported decreased risk of recurrent VTE among patients who received 9‐month extended treatment with VKAs (warfarin or acenocoumarol) following 3 months of anticoagulant therapy. Both studies also reported that the benefit from extended anticoagulant therapy was not maintained following treatment discontinuation 27, 28. Summarizing the clinical trial (eg, AMPLIFY‐EXT [apixaban vs placebo] and RE‐SONATE [dabigatran vs placebo]) evidence base for recurrent VTE risk and duration of anticoagulant therapy, Smilowitz et al.…”
Section: Discussionmentioning
confidence: 99%
“…One study on PE27 and a second study on DVT28 have reported decreased risk of recurrent VTE among patients who received 9‐month extended treatment with VKAs (warfarin or acenocoumarol) following 3 months of anticoagulant therapy. Both studies also reported that the benefit from extended anticoagulant therapy was not maintained following treatment discontinuation 27, 28. Summarizing the clinical trial (eg, AMPLIFY‐EXT [apixaban vs placebo] and RE‐SONATE [dabigatran vs placebo]) evidence base for recurrent VTE risk and duration of anticoagulant therapy, Smilowitz et al.…”
Section: Discussionmentioning
confidence: 99%
“…After duplicates were removed, 928 citations were screened for inclusion. Of those, 890 and 27 citations were excluded at the abstract and full text level, respectively, leaving 11 citations reporting 12 unique trials [9][10][11][12][13][14][15][16][17][18][19] (Table 1). Rivaroxaban 12 and idraparinux 16 were each evaluated in comparison to placebo in individual trials ( Figure 2).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…13 VKAs were compared to either placebo or control (i.e., discontinuation of VKA therapy with no placebo administration) in five trials. 9,10,[17][18][19] Finally, aspirin was compared to placebo in two trials. 14,15 Six trials were judged to…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations